2015
DOI: 10.1007/s11270-015-2611-3
|View full text |Cite
|
Sign up to set email alerts
|

Azo Dye Acid Blue 29: Biosorption and Phytotoxicity Test

Abstract: Many products contain dyes, such as fabrics. However, most of the industry-generated waste is improperly handled, which causes serious environmental problems for the bodies of water that receive textile effluents. This study aimed to analyze the effect of biosorbents and biosorption techniques on decolorizing the textile azo dye Acid Blue 29 in an aqueous solution employing pine sawdust. Pine sawdust is low-cost substrate with minor environmental impact. A toxicity test was performed with Lactuca sativa seeds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 15 publications
0
4
0
1
Order By: Relevance
“…• o controle negativo com água destilada, totalizando nove tratamentos estatísticos realizados em triplicata, montados em blocos casualizados (SOBRERO; RONCO, 2004;CORSO, 2014;GUARI et al, 2015).…”
Section: Metodologiaunclassified
“…• o controle negativo com água destilada, totalizando nove tratamentos estatísticos realizados em triplicata, montados em blocos casualizados (SOBRERO; RONCO, 2004;CORSO, 2014;GUARI et al, 2015).…”
Section: Metodologiaunclassified
“…IR and UV-vis spectra were recorded on a Thermoscientific Nicolet 8700 Spectrometer. 1 H (300 MHz) and 13…”
Section: Synthesis Of the Ilsmentioning
confidence: 99%
“…The presence of dyes in natural aquatic recipients can affect water transparency, and it has been demonstrated that they affect photosynthetic activity . Some of the degradation products are aromatic rings and aryl amides, which are frequently more carcinogenic and toxic than basic compounds …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finishing is the process of using chemical chemicals to improve the appearance and feel of a textile. Permanent press procedures such as waterproofing and softening, as well as antistatic treatment, can extend the life of water and stain-resistant textiles [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%